Fundamental understanding of microwave assisted ring-opening polymerisation and co-polymerisation - Greenhalgh, Edward T. (2014)
The work presented in the thesis attempted to gain in-depth understanding of the effect that the microwave energy has on various facets of the ring-opening polymerisation of cyclic esters with a view to synthesising novel bio-degradable homopolymers, branched structures and copolymers. Chapter 1 introduces the various synthetic polymer procedures and lists possible final product architectures. The main technique that is used throughout this thesis, ring-opening polymerisation, is discussed in great detail. The various targeted linear aliphatic polyesters are introduced. Finally, the fundamental theory behind microwave dielectric heating is discussed. Chapter 2 outlines the various characterisation techniques that are used to analyse the various synthesised materials throughout the work in this thesis. The polymerisation techniques used, particularly using the microwave reactor, is also discussed. In Chapter 3, the effect that microwave heating has upon the homopolymerisation of poly(ε-caprolactone) is investigated. Detailed analysis of the dielectric properties of the reagents and accurate temperature monitoring is applied at various stages of the reaction mechanism to compare and contrast the effect of microwave and conventional heating. Chapter 4 describes the impact that microwave energy has upon the copolymerisation reactions when a second cyclic ester is introduced, D/L-lactide. Various procedures are utilised in an attempt to synthesise bio-degradable block copolymers with interesting mechanical properties and degradation rates. The dielectric properties of the reagents and their polymer structures are used to rationalise any experimental observations. The work presented in Chapter 5 investigates the synthesis of branched polymers using a di-lactone branching agent, composed to two joined ε-CL units. Various analytical techniques are employed to guarantee successful branching. The effect of microwave energy is scrutinised, with a view to creating faster rates of reaction and altering the final product structure using direct dielectric heating. Finally, Chapter 6 provides the overall conclusions obtained from the work presented in this thesis, before providing possible routes of subsequent study for further research into this area.